PENTINGNYA PENGETAHUAN PERLINDUNGAN HUKUM TERHADAP HAK AZASI HEWAN PELIHARAAN BAGI WARGA NEGARA INDONESIA - Delila Kania; Deni Zein Tarsidi; Darda Abdullah Sjam; Zakki Abdillah Sjam (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT Pets are animals whose lives partially or completely depend on humans for certain purposes. Humans as animal owners who keep animals are obliged to fulfill the welfare of the animals they care for. The obligations of pet owners are contained in statutory regulations. The purpose of this study is to find out how the state through applicable legal provisions provides animal rights protection for pets. Knowledge of legal protection for pets must be known and implemented by all Indonesian citizens. This research uses literature study method. The results of the research show that the law in Indonesia stipulates that all matters related to animal welfare efforts are a joint obligation between the central government, regional governments, and the community. However, legal protection for animals that are not kept by humans and live on the streets or in an open environment is not specifically regulated in the legal provisions that apply in Indonesia. Legal protection that is subject to severe sanctions is more aimed at wild animals protected by the state because their habitat is almost extinct.